Vprašanja tradicije Škofjeloškega pasijona - Ogrin, Matija (Slavistična revija, 2008)
The examination of the Škofja Loka Passion Play from the viewpoint of textual criticism showed that the date of its origin (1721) had not been sufficiently verifed and that it is harder to date the origin than has been thought. It was also shown that in addition to the text itself, one must take into account other documents, which indicate that in Škofja Loka, an older tradition of staging pssion plays in Slovene had existed before Father Romuald.
Keywords: pasijonske igre; Romuald, oče, 1676-1748; Slovene literature; slovenska dramatika; slovenska književnost; Škofja Loka Passion Play; Škofjeloški pasijon